English Major Students’ Perceptions of Academic Writing: A Struggle between Writing to Learn and Learning to Write - Sağlamel, Hasan; Kayaoğlu, Mustafa Naci (Journal of History Culture and Art Research, 2015)
English Major Students’ Perceptions of Academic Writing: A Struggle between Writing to Learn and Learning to Write Abstract Even though writing as a language skill takes a back seat especially with reference to the natural order hypothesis, appreciation of writing in academic settings propel learners to challenge the validity of this order. It is not surprising therefore that writing deserves a higher priority in academic settings due much to its immediate practical application in a variety of academic tasks such as examination questions, essays, research reports, dissertation thesis and so on. In line with this constant practice with writing, English majoring students are quite usually subject to production of texts in the academic essay genre and desire to position themselves in academic discourse community through following the desired academic conventions. However, a considerable number of students fail to achieve the desired proficiency; cultural variations intrude into the language classrooms and differences in meaning learners attach to the writing activities are evident, which makes it necessary to explore students’ perceptions from academic writing courses. To this end, questionnaires on students’ writing efficacy were distributed to the freshman students enrolled in Academic Writing class, and interviews were carried out to have a broader understanding of the expectations from the course. Data from the questionnaire were analyzed using the SPSS and content analysis was employed to analyze the interviews.